2009
DOI: 10.1007/978-3-642-00199-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Toward Non-security Failures as a Predictor of Security Faults and Failures

Abstract: Abstract. In the search for metrics that can predict the presence of vulnerabilities early in the software life cycle, there may be some benefit to choosing metrics from the non-security realm. We analyzed non-security and security failure data reported for the year 2007 of a Cisco software system. We used non-security failure reports as input variables into a classification and regression tree (CART) model to determine the probability that a component will have at least one vulnerability. Using CART, we ranke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The weaker metrics have less significant splits, although the p-values are below 0.05, than the strongly-correlated metric. However, our observations in [12], and in comparison of the results presented here with those in [13], we find that weaklycorrelated metrics can lead to more splits than strongly-correlated metrics, and that many splits can yield good separation between attack-prone and not attack-prone components. …”
Section: Predictive Modelssupporting
confidence: 59%
See 1 more Smart Citation
“…The weaker metrics have less significant splits, although the p-values are below 0.05, than the strongly-correlated metric. However, our observations in [12], and in comparison of the results presented here with those in [13], we find that weaklycorrelated metrics can lead to more splits than strongly-correlated metrics, and that many splits can yield good separation between attack-prone and not attack-prone components. …”
Section: Predictive Modelssupporting
confidence: 59%
“…We do not restrict our metrics to the security realm, however. Our prior work [9,12,13] indicates that non-security failures are positively correlated with security failures, and we therefore do not exclude non-security warnings as candidate metrics.…”
Section: Candidate Metricsmentioning
confidence: 99%
“…Gegick et al [14] investigated whether non-security failure reports could be used to predict whether a given component is vulnerable. In the context of a Cisco software system, the authors found a 0.4 correlation between security faults and non-security failures.…”
Section: Vulnerability Prediction Modelsmentioning
confidence: 99%
“…Gegick et al used code-level metrics such as lines of code, code churn, and number of static tool alerts [8] as well as past non-security faults [7] to predict security faults. In the most recent work, Gegick et al achieved a precision of 0.52 and a recall of 0.57.…”
Section: Related Workmentioning
confidence: 99%